2023
DOI: 10.1177/09697330231191277
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues in long-term care settings: Care workers’ lived experiences

Anna-Liisa Arjama,
Riitta Suhonen,
Mari Kangasniemi

Abstract: Background Professional care workers face ethical issues in long-term care settings (LTCS) for older adults. They need to be independent and responsible, despite limited resources, a shortage of skilled professionals, global and societal changes, and the negative reputation of LTCS work. Research aim Our aim was to describe the care workers’ lived experiences of ethical issues. The findings can be used to gain new perspectives and to guide decision-making to improve the quality of care, occupational well-being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…However, there are at least two compelling reasons for considering ethical self-efficacy directly. First, caregivers routinely have to make ethical decisions (Arjama et al, 2023;Preshaw et al, 2016;Strech et al, 2013). Navigating such ethical issues can be challenging, and several studies have shown that professional caregivers of people with dementia find this process stressful (Chen & Highfill, 2023;Costello et al, 2019), notably when compared to non-dementia caregivers (Ory et al, 1999;Sheehan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are at least two compelling reasons for considering ethical self-efficacy directly. First, caregivers routinely have to make ethical decisions (Arjama et al, 2023;Preshaw et al, 2016;Strech et al, 2013). Navigating such ethical issues can be challenging, and several studies have shown that professional caregivers of people with dementia find this process stressful (Chen & Highfill, 2023;Costello et al, 2019), notably when compared to non-dementia caregivers (Ory et al, 1999;Sheehan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Impaired capacity means that people with dementia increasingly require assistance to make medical decisions and eventually, the majority of people with dementia require strong support in terms of long-term care (sm-Rahman et al, 2022). The increased need for support in long-term care involves several specific ethical issues, such as the conflict between respecting the self-determination of people with dementia and ensuring that their well-being is protected, as well as considering whether to tell the truth to people with dementia even if this harms them (Arjama et al, 2023; Preshaw et al, 2016; Schou-Juul & Lauridsen, 2024; Strech et al, 2013). Such ethical issues are extremely prevalent in dementia care and caregivers are tasked with making ethical judgments on a day-to-day basis (Lewenson & Truglio-Londrigan, 2007; Ulrich et al, 2010; Varcoe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%